Comparative Analysis of Hyaluronic Acid and Corticosteroid Injections in the Treatment of TMJ Osteoarthritis - Uddin, Mohammad Nasir; Haque, Mohammad Sazzadul; Ashrafuzzaman, Mohammad; Ullah, Mohammad Nayeem (Journal of Monno Medical College, 2026)
Background: Temporomandibular joint (TMJ) osteoarthritis is a common disorder that results in pain, dysfunction, and limited mouth opening. Intra-articular injections of hyaluronic acid (HA) and corticosteroids are frequently utilized in the management of TMJ osteoarthritis, yet their comparative efficacy remains unclear. Objective: The aims to compare the clinical outcomes of intra-articular hyaluronic acid versus corticosteroid injections in the treatment of temporomandibular joint osteoarthritis. Methodology: This randomized controlled trial was conducted in the Department of Department of Orthopedics, Monno Medical college and Hospital, Manikganj, Bangladesh and Department of Otolaryngology, Monno Medical College and Hospital, Manikganj, Bangladesh which was included 42 participants with TMJ osteoarthritis. Participants were randomly assigned to receive either intra-articular hyaluronic acid (n=21) or corticosteroid (n=21) injections. Clinical outcomes were assessed at baseline, and at 4-, 8-, and 12-weeks post-treatment. Primary outcomes included changes in visual analog scale (VAS) pain scores and mouth opening measurements. Secondary outcomes included adverse events. Results: Both treatment groups demonstrated significant improvements in VAS pain scores and mouth opening over the 12-week study period. However, at Week 12, the hyaluronic acid group showed a significantly greater reduction in pain (p=0.042) and improvement in mouth opening (p=0.022) compared to the corticosteroid group. No significant differences were observed between the groups regarding adverse events. Conclusion: Intra-articular hyaluronic acid injections provide superior long-term pain reduction and improvement in mouth opening compared to corticosteroid injections in the treatment of TMJ osteoarthritis. Both treatments were well-tolerated with minimal adverse effects. Journal of Monno Medical College, June, 2025; 11(1) : 33-38